Pengaruh Sistem Keuangan Desa dan Sistem Pengendalian Intern Pemerintah Terhadap Akuntabilitas Pengelolaan Dana Desa - Arfiansyah, Mufti Arief (IAIN Surakarta, 2020)
This study aims to determine the effect of the Village Finance System (Siskeudes) and the Government Internal Control System (SPIP) on the accountability of village fund management. This study refers to a quantitative approach to the population of villages in Wonogiri District. Determination of the sample by random sampling technique. The process of collecting data uses the questionnaire method. Respondents in this study were the Village Head and Village Secretary. Data analysis uses multiple regression analysis. The results showed that 1) The Village Financial System (SISKEUDES) affected the accountability of village fund management. 2) Government Internal Control System (SPIP) influences the accountability of village fund management.Keywords: Village Fund Management Accountability, Village Financial System, Government Internal Control System.JEL Classification Codes: C12, P25, R50